In vivo characterization of the maturation steps of a pigment dispersing factor neuropeptide precursor in the Drosophila circadian pacemaker neurons. - Lee, G.G.; Zeng, K.; Duffy, C.M.; Sriharsha, Y.; Yoo, S.; Park, J.H. (Genetics, 2023)
Pigment dispersing factor (PDF) is a key signaling molecule coordinating the neuronal network associated with the circadian rhythms in Drosophila. The precursor (proPDF) of the mature PDF (mPDF) consists of 2 motifs, a larger PDF-associated peptide (PAP) and PDF. Through cleavage and amidation, the proPDF is predicted to produce cleaved-PAP (cPAP) and mPDF. To delve into the in vivo mechanisms underlying proPDF maturation, we generated various mutations that eliminate putative processing sites and then analyzed the effect of each mutation on the production of cPAP and mPDF by 4 different antibodies in both ectopic and endogenous conditions. We also assessed the knockdown effects of processing enzymes on the proPDF maturation. At the functional level, circadian phenotypes were measured for all mutants and knockdown lines. As results, we confirm the roles of key enzymes and their target residues: Amontillado (Amon) for the cleavage at the consensus dibasic KR site, Silver (Svr) for the removal of C-terminal basic residues from the intermediates, PAP-KR and PDF-GK, derived from proPDF, and PHM (peptidylglycine-?-hydroxylating monooxygenase) for the amidation of PDF. Our results suggest that the C-terminal amidation occurs independently of proPDF cleavage. Moreover, the PAP domain is important for the proPDF trafficking into the secretory vesicles and a close association between cPAP and mPDF following cleavage seems required for their stability within the vesicles. These studies highlight the biological significance of individual processing steps and the roles of the PAP for the stability and function of mPDF which is essential for the circadian clockworks.